ADSORPSI LOGAM Pb dan Cu DARI PELUMAS BEKAS MENGGUNAKAN BLENDING SELULOSA ASETAT-KITOSAN - Fitra Langgeng Mangesti; Husain Sosidi; Prismawiryanti; Syamsuddin (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2019)
Research on adsorption of Pb and Cu metals from used lubricants has been carried out using cellulose acetate-chitosan blending which aims to determine the best ratio and pH between cellulose acetate and chitosan which can adsorb metal Pb and Cu from used lubricants. Cellulose acetate was synthesized through the acetylation method using cellulose extracted from palm fiber coir. The obtained cellulose acetate is brown fine powder with a yield of 62% and has a water content of 20%. Cellulose acetate was characterized using FT-IR while adsorption of Pb and Cu metals from used lubricants using AAS. The results of FT-IR analysis showed the formation of cellulose acetate with an absorption band of 1637.56 cm-1 which proved the presence of carbonyl groups (C = O). The AAS results showed that the best ratio and pH to absorb Pb and Cu metals in used lubricants is 3:1 with pH 6. Keywords: palm oil coir, acetate cellulose, chitosan, used lubricants